Ablasi 3-Dimensi pada Pasien dengan Takikardia Right Ventricular Out-flow Track (RVOT) Origin: Pengalaman Pertama di RSUD Dr. Saiful Anwar Provinsi Jawa Timur - Cik, Kahadi; Rizal, Ardian (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Background: Premature ventricular complexes (PVCs) occur commonly in general population. It can occur in patient without structural heart disease as well as those with any form of cardiac disease. Commonly PVCs are asymptomatic, but in patients with frequent PVCs causing palpitations, syncope or dizziness, easily to fatigue, or shortness of breath. PVCs has been connected with a more than two-fold higher risk of cardiovascular events including stroke, mortality and also associated with arrhythmias or cardiomyopathy. Medications can be used to suppress PVCs but when drug therapy is ineffective, PVC ablation is reasonable to eliminate symptoms and treat or prevent PVC-induced cardiomyopathy. Case Presentation: A hypertension and menopause, 57-year-old woman, frequently complained about palpitation with shortness of breath, dizziness and sometimes near syncope since 2017, occurring both at rest and with mild activities. After serial examinations, found Frequent PVC (39%) with RVOT-Origin and reduced ejection fraction (EF 48%), then conclude with Suspect Tachycardia Induced cardiomyopathies. She performs cardiac electrophysiological study and continue with 3-Dimentional Ablation with Radiofrequency (RFA) at RVOT in Saiful Anwar Hospital, that is The First 3-Dimension Ablation in East Java. 1 year follow up shows no recurrency and successful to improve quality of life of the patient Discussion: According to guideline, catheter ablation is class I recommendation for patients with symptomatic outflow tract ventricular arrhythmias if medications are ineffective, not tolerated, or patient’s choose Conclusion: Three-Dimensional Ablation at patient with Right Ventricular Outflow Track Tachycardia, can successfully eliminate PVCs with no recurrency in 1 year follow-up.